Clinical efficacy of Methylene Blue mediated antimicrobial Photodynamic Therapy (PDT) using 680 nm Diode Laser in patients undergoing Open Flap Debridement: An Original Research - Soundarya Singh; Manisha Rout; Mayur Kaushik; Shilpa Sharma; Aprajita Srivastava (Journal of Oral Biology and Craniofacial Research)
Background: Inflammatory periodontal disease caused by dental plaque is characterised by the clinical signs of inflammation and loss of periodontal tissue support. The mechanical removal of this biofilm and adjunctive use of antibacterial disinfectants and antibiotics have been the conventional methods of periodontal therapy. The possibility of the development of resistance to antibiotics by the target organism has led to the development of a new antimicrobial concept with fewer complications. Photodynamic therapy (PDT) involves the use of low-power lasers with appropriate wavelengths to kill microorganisms treated with a photosensitiser drug. PDT could be a useful adjunct to mechanical as well as antibiotics in eliminating periodontal-pathogenic bacteria. Methods: The patients selected were randomly divided into two groups. In the test group, Open Flap Debridement (OFD) with Methylene Blue-mediated Antimicrobial Photodynamic Therapy (PDT) using 680 nm Diode Laser application was done, and in the control group, OFD alone. Results: The results of this study showed that diode laser irradiation (680 nm) combined with methylene blue dye reduced pocket probing depth and gingival bleeding by up to 95.85 % in the group treated with PDT with 5 min of irradiation. Conclusions: The adjunctive use of photodynamic therapy with Diode 680 nm Laser and Methylene Blue Photosensitiser can be beneficial in reducing pocket probing depth, plaque index, and gingival bleeding index. Antimicrobial photodynamic therapy may hold promise as a substitute for currently available chemotherapy in the treatment of periodontal and peri-implant disease and in endodontic therapy.